A Segmentation of Lifestyle of S1 Students Faculty of Islamic Economics and Business University of Islam Kiai Haji Achmad Siddiq Jember - Mirza, Mohammad (Journal of Islamic Economics Perspectives, 2021)
ABSTRACT Segmentation is not only used by companies in determining policies to dominate the market, but segmentation is able to provide an overview or information on human lifestyles, especially students of the Faculty of Economics and Islamic Business at Kiai Haji Achmad Siddiq State Islamic University Jember. In the world of education, segmentation is able to provide information about students, then the information will be used to compile academic programs that have the essence of the character of students. This research uses action research methods or action testing without research, that is, researchers do not carry out systematic research according to the rules of research methodology. This is because the researcher is a lecturer at the Faculty of Economics and Islamic Business at the State Islamic University of Kiai Haji Achmad Siddiq Jember. In this study, students of the Faculty of Economics and Islamic Business have three criteria or segments, namely dynamic students, identity seeking students and conservative students.